Nilai Didaktik Moralistik Dalam Serat Wasita Rini Karya Ki Hadjar Dewantara - Akbar Al Masjid; Sarwiji Suwandi (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
This study focuses on the study of the value of moral education / didactic moralistic values contained in Ki Hadjar Dewantara's Serat Wasita Rini through content analysis. The data analysis methods and techniques used are the content analysis method of the semiotic model. Moral education can be equated with the terms ethical education, character education, value education or affective education. The results of the didactic moralistic value research contained in Serat Wasita Rini are as follows: 1) A woman should always maintain the norms of decency and morality; 2) Safeguarding themselves and their honor; 3) Women, do not like to order arbitrarily; 4) self-control; 5) A woman must be conscientious and clever at sorting out good and bad things; 6) Women are required to have creative intelligence, taste, and intention (morals)